A Functional Model of Kitsch and Art: Linking Aesthetic Appreciation to the Dynamics of Social Motivation - Ortlieb, Stefan A.; Carbon, Claus-Christian (Frontiers in Psychology, 2019)
With the advent of modernity, change and novelty have become the core values of artistic production. At the same time the derogatory term “kitsch” was coined to contrast truly ground-breaking artistic achievements. In this article, we argue that kitsch and avant-garde art ideally represent two complementary types of aesthetic experience: a fluent one that allows for immediate emotional gratification (kitsch) and a disfluent one that requires cognitive elaboration (art). We make a case that preferences for the one or the other are dynamically related to a set of conflicting needs that constitute the basic dilemma of human attachment behavior: needs for safety and intimacy versus needs for arousal and autonomy. Based on the Zurich Model of Social Motivation, we hypothesize that social distance regulation and aesthetic liking are synchronized via notions of self-efficacy and autonomy: Whenever we feel safe and self-sufficient, an appetence for arousal (curiosity) is likely to arise that increases our interest in unfamiliar conspecifics as well as in innovative, cognitively challenging aesthetic stimuli (art). By contrast, when we feel vulnerable and dependent, a longing for safety and relatedness (nostalgia) attracts us not only to familiar and trustworthy individuals but also to conventional aesthetic stimuli that are charged with positive emotions (kitsch). This biopsychosocial framework offers an integrative perspective on dynamics of aesthetic liking in that it unites a wide variety of phenomena from anthropology, developmental and differential psychology with concepts and findings from art history, art sociology, and empirical aesthetics.